2018
DOI: 10.28991/cej-03091144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fibre Length on the Behaviour of Polypropylene Fibre Reinforced Cement Concrete

Abstract: Concrete being a mixture of cement, aggregates (fine and coarse) and water, can be used in vast range of applications. It has excellent durability and availability which are its main advantages. Though, concrete is strong in compression it is comparatively weak in tensile loading. Over the years various materials have been used to reinforce concrete to withstand the tensile stresses. Polypropylene fibre is one such fibre which comes in varied sizes, is nowadays being utilized to reinforce concrete. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 10 publications
(12 reference statements)
1
16
0
1
Order By: Relevance
“…In contrast to the behaviour observed during the compressive strength testing, the M3 and M4 samples with 0.25% and 0.30% PP fibres exhibited higher flexural strength than the control sample M1. Similar behaviour was also reported by [4]. In the interfacial zone, the micro-cracks are initially developed when the concrete is subjected to tensile stresses.…”
Section: Flexural Strengthsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to the behaviour observed during the compressive strength testing, the M3 and M4 samples with 0.25% and 0.30% PP fibres exhibited higher flexural strength than the control sample M1. Similar behaviour was also reported by [4]. In the interfacial zone, the micro-cracks are initially developed when the concrete is subjected to tensile stresses.…”
Section: Flexural Strengthsupporting
confidence: 87%
“…al. [4] reinforced concrete with two different PP fibre lengths (12.7 mm and 25.4 mm) and three different contents (0.20%, 0.25% and 0.30%). It was found that fibre length had a significant influence on the properties of concrete.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have done the study of enhancement of the properties of LFC by the inclusion of short fibres such as sisal fibres [14], kenaf fibres [15][16][17], oil palm fibres [15,18], polypropylene fibres [15,16], and AR-glass and steel fibres [15]. However, some of the materials have a negative impact on the long-term performance of LFC such as deterioration of natural fibre [19], and corrosion of the reinforcing steel [20]. Thus, in this research, authors have explored the potentiality of continuous fibres, namely, fibremesh, as an enhancement to the properties of LFC, this has not being practiced yet in such types of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the concrete's infrastructures is constructed using concrete, which is the most preferred construction and building material in the construction industry . The popularity of concrete has increased due to its availability, flexibility and durability (Memon et al, 2018), that is why concrete has been utilized in vast civil engineering applications ranging from the construction of foundations, retaining walls to bridges and dams (Sandhu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%